Reliability and Validity of Survey Instruments to Measure Work-Related Fatigue in the Emergency Medical Services Setting: A Systematic Review. (15th February 2018) - Patterson, P. Daniel; Weaver, Matthew D.; Fabio, Anthony; Teasley, Ellen M.; Renn, Megan L.; Curtis, Brett R.; Matthews, Margaret E.; Kroemer, Andrew J.; Xun, Xiaoshuang; Bizhanova, Zhadyra; Weiss, Patricia M.; Sequeira, Denisse J.; et al.
Abstract: Background : This study sought to systematically search the literature to identify reliable and valid survey instruments for fatigue measurement in the Emergency Medical Services (EMS) occupational setting.Methods : A systematic review study design was used and searched six databases, including one website. The research question guiding the search was developed a priori and registered with the PROSPERO database of systematic reviews: "Are there reliable and valid instruments for measuring fatigue among EMS personnel?" (2016:CRD42016040097). The primary outcome of interest was criterion-related validity. Important outcomes of interest included reliability (e.g., internal consistency), and indicators of sensitivity and specificity. Members of the research team independently screened records from the databases. Full-text articles were evaluated by adapting the Bolster and Rourke system for categorizing findings of systematic reviews, and the rated data abstracted from the body of literature as favorable, unfavorable, mixed/inconclusive, or no impact. The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) methodology was used to evaluate the quality of evidence.Results : The search strategy yielded 1, 257 unique records. Thirty-four unique experimental and non-experimental studies were determined relevant following full-text review. Nineteen studies reported on the reliability and/or validity of ten different fatigue survey instruments. Eighteen different studies evaluated the reliability and/or validity of four different sleepiness survey instruments. None of the retained studies reported sensitivity or specificity. Evidence quality was rated as very low across all outcomes.Conclusions : In this systematic review, limited evidence of the reliability and validity of 14 different survey instruments to assess the fatigue and/or sleepiness status of EMS personnel and related shift worker groups was identified.